Semiotic Citizenship and the Construction of Belonging in Multilingual Public Spaces - Aulia Rahman (Generasi Sains Indonesia, 2025)
This study examines how semiotic citizenship is enacted within multilingual public spaces and how language, visibility, and emotion shape experiences of belonging in the urban environment. It focuses on how individuals negotiate recognition and participation through linguistic and visual signs distributed across the city’s semiotic landscape. The research was conducted in three contrasting urban locations a traditional market, a transportation terminal, and a municipal plaza chosen for their different semiotic ecologies and levels of institutional regulation. Using a qualitative ethnographic design grounded in semiotic landscape analysis, data were collected through visual documentation, participant observation, and semi-structured interviews with twenty-five participants, including traders, migrants, residents, and municipal officers. Multimodal discourse analysis and thematic coding were employed to interpret how signs operate as symbolic resources of citizenship. The findings show that multilingual signage functions as a semiotic performance of belonging where linguistic hierarchies, creative hybridity, and emotional attachment intersect. While formal spaces reinforce institutional authority through standardized languages, informal areas enable vernacular and hybrid expressions that serve as grassroots visibility. Participants associated the public presence of their languages with emotional recognition, shared identity, and cultural memory. Overall, semiotic citizenship emerges as an affective and participatory practice, continuously written into the multilingual textures of everyday urban life.